GREEN ACCOUNTING : A BIBLIOMETRICS ANALYSIS - Husda, Anggun Permata (JURNAL AKUNTANSI BARELANG, 2024)
A continuity method that is in line with recent advancements in the accounting industry is green accounting. The economy is one of the many areas that green accounting affects. Information that is precise, accountable, and transparent is provided to stakeholders through the application of Green Accounting to environmental accounting. The most important research publications in green accounting as well as statistical trends in the field are the focus of this study. Research data was gathered and examined from 1000 publications using the keyword "Green Accounting" on Google Scholar using the VOSviewer software. The results of research on green accounting conducted over the last ten years, from 2014 to 2024, are significant to study and a subject that academics frequently write about, according to the processed data. The research results provide a systematic contribution to Green Accounting research.